Comparison of Quality of Life Before and After Cosmetic Rhinoplasty among People Who Attended Plastic Surgery Clinics and Estimating Its\' Cost in Tehran - Marita Mohammadshahi; Abolghasem Pourreza; Aboali Vedadhir; Parvaneh Heidari Orojlo; Mahmod Mahmodi; Feizallah Akbari (Tehran University of Medical Sciences, 2016)
Background and Aim: Cosmetic surgery rhinoplasty, has dramatically been increased during the last two decades. This study aims to explore its effects on the quality of life of individuals gone under the surgery. Materials and Methods: This was a descriptive and analytical study which was performed as a cross-sectional study. From all plastic surgery clinics in Teheran, 25 clinics were selected randomly as the site of study. In the next step 110 patients undergone rhinoplasty were selected randomly from these clinics. Collected data was analyzed by Spss17. Results: Findings revealed that, the mean score of quality of life before and after surgery was statistically significant. While mean score of general benefits increased the score of social support and physical health was decreased after the surgery. The most motivating factors for surgery were external factors. In addition there was a positive correlation between quality of life and the time of interview. Also the mean cost of surgery was increased. Conclusion: Overall quality of life among study population was decreased. It could be because of unnecessary surgeries, medical errors, and etc. The reduction for social support may be resulted from unacceptable consequences of rhinoplasty particularly in terms of appearance. Physical health of respondents was negatively affected by rhinoplastiy surgery. Malfunctions of upper respiratory system after rhinoplastiy surgery is known as the main reason for it. Correlations between the times of surgery and interview suggest a long term assessment of impacts of such surgeries.